History and Evolution of Corporate Social Responsibility - Imam Abdul Rahman (Al-Qanṭara, 2022)
The concept of Corporate Social Responsibility has been around for a very long time and has undergone many transformations since its inception (CSR). However, there is not a historical review that depicts the development of the academic field that can be found in the academic literature. comprehension of the idea in conjunction with national and international happenings that had an impact on the social expectations in regard to proper conduct in the workplace. The purpose of this paper is to offer a unique historical perspective on the perspective on the evolution of CSR as a conceptual paradigm by reviewing the most relevant factors that its understanding and definition have been shaped by a number of factors, including academic contributions, international policies, and important happenings in both the social and political spheres. A comprehensive literature review is the method that is used to accomplish this goal. examines the academic contributions and public events that have had the most significant impact on the evolutionary process. procedure for CSR and the manner in which they have carried it out. The findings demonstrate that there has been an increase in the understanding of corporate responsibility. evolved from being restricted to the production of profits only to include a wider range of responsibilities to the most recent belief system. that the creation of shared value should be the primary responsibility of companies. The findings also suggest that in light of the fact that Along with the shifting social expectations of how businesses should behave, the concept of Corporate Social Responsibility also evolved. The results obtained imply that corporate social responsibility (CSR) maintains its importance within the context of the academic literature and that it is likely to continue to play a role in business vocabulary at least in the short term, and as a consequence, the authors present a plausible future for CSR that takes into account these shifts in terminology. taking into account its development throughout its history. In conclusion, this study paves the way for additional academic research in the future to investigate how CSR works. can assist in meeting the most recent social expectations that a primary business objective should be the creation of shared value, which in turn can may have tangible effects if corporate social responsibility initiatives are carried out keeping this in mind.